Melaka Botanical Park Services Management System - Mazlan, Muhammad Ariffudin; Norhanim Selamat (Applied Information Technology And Computer Science, 2021)
Abstract: Service Management System is to facilitate when dealing with data or information from customers. Taman Botanikal Melaka uses manual methods to manage their service information to customers. Customers need to go to the park and queue at the counter to fill in the information. Manual systems are now becoming less relevant as humans are unable to deal with work processes with a large number of papers to analyze growing data. therefore, this system was developed to facilitate the process of renting the services provided at the Taman Botanikal Melaka by customers without going to the counter and writing information. The methodology used to manage the development of this system is a prototype model. The programming languages used are Hypertext Preprocessor (PHP) and Hypertext Mark-up Language (HTML) and MySQL database. This system can be used for the Taman Botanikal Melaka customer who wants to use the provided services. This system can manage various information to the services. With the development of this system, users only need to login into the system to make the reservation and this system also provided all services that have at Taman Botanikal Melaka then it will save the users time and energy to go the place. This service management system is much better than any existing system for managing service and customer data, as well as for managing the ordering and renewal process.